Paths of West Indian hurricanes for 11 years : 1947-1957 inclusive / Cravens, Dargan & Company, 1958 - Cravens, Dargan & Company Special Risks (Houston, Tex. : Cravens, Dargan & Co., 1958)
Showing Hurricanes Not Touching Texas or Louisiana Coast Line and Hurricanes Touching Texas or Louisiana Coast Line; Color;